Thermoreflectance and micro-Raman measurements of the temperature distributions in broad contact laser diodes - Ochalski, Tomasz J.; Piwoński, Tomasz; Wawer, Dorota; Pierściński, Kamil; Bugajski, Maciej; Kozłowska, Anna; Maląg, Andrzej; Tomm, Jens W. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
In this paper we describe a number of optical techniques suitable for estimation of the semiconductor surface temperature. High spatially resolved thermoreflectance will be shown as a powerful tool to measure temperature distribution at the laser diode front facet. For determination of the absolute value of the front facet temperature we use micro-Raman spectroscopy. Both techniques will be presented as a complementary ways to determine surface temperature distribution on the working laser diode.
Optica Applicata, Vol. 35, 2005, nr 3, s. 479-484
Keywords: optyka; thermoreflectance; Raman spectroscopy; semiconductor laser